The Ambrose deception - Ecton, Emily (Los Angeles : New York : Disney/Hyperion, 2018)
Three Chicago students, Melissa, Wilf, and Bondi, are unlikely participants in a competition for a ten thousand-dollar scholarship, unaware that there is much more at stake.
Keywords: Contests -- Fiction; Puzzles -- Fiction; Inheritance and succession -- Fiction; Chicago (Ill.) -- Fiction